2012
DOI: 10.2146/ajhp110604
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a rapid peptide nucleic acid fluorescence in situ hybridization assay on treatment of Candida infections

Abstract: Implementing a PNA FISH test to identify Candida species from yeast-positive blood cultures in conjunction with a pharmacy-driven antimicrobial stewardship protocol decreased the time to targeted antifungal therapy and the time to culture clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 9 publications
4
91
0
3
Order By: Relevance
“…To try to further improve the time to targeted therapy, we will implement an antimicrobial stewardship intervention in which CHROMagar results will be paged to an on-call pharmacist who will then collaborate with the medical team to switch to targeted therapy. This approach has previously been successful at our institution (9). Regardless of our future endeavors, this study supports the idea that rapid culture-based detection of MRSA and MSSA plays a role in antimicrobial stewardship by decreasing the time that it takes to place patients on targeted antimicrobial therapy.…”
Section: Discussionsupporting
confidence: 72%
“…To try to further improve the time to targeted therapy, we will implement an antimicrobial stewardship intervention in which CHROMagar results will be paged to an on-call pharmacist who will then collaborate with the medical team to switch to targeted therapy. This approach has previously been successful at our institution (9). Regardless of our future endeavors, this study supports the idea that rapid culture-based detection of MRSA and MSSA plays a role in antimicrobial stewardship by decreasing the time that it takes to place patients on targeted antimicrobial therapy.…”
Section: Discussionsupporting
confidence: 72%
“…These effects are more pronounced in patients with BSI where use of rapid diagnostics coupled with pharmacy intervention to improve antibiotic optimization resulted in significant reductions in hospital length of stay (LOS), healthcare costs, and mortality. [8][9][10][11][12][13] To date, the role of rapid diagnostics in ASPs has largely been studied in tertiary or quaternary care medical centers with dedicated infectious diseases pharmacists, complex patient populations, and robust clinical laboratory services. Thus, limited data are available in lower acuity community hospital settings.…”
mentioning
confidence: 99%
“…False-positive S. pneumoniae results do not limit the utility of the assay, as we were still able to develop a treatment algorithm to promote the use of targeted regimens based on the results generated by the BC-GP assay. Although we have previously shown that a pharmacy-based intervention strategy is effective at our institution (8), the effectiveness of our BC-GP algorithm for streptococci and enterococci will need to be measured.…”
mentioning
confidence: 99%